The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1111/j.1476-5381.1988.tb11463.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artificial respiratory volume on the cardiovascular responses to an α1‐ and an α2‐adrenoceptor agonist in the air‐ventilated pithed rat

Abstract: 1 The effect of varying artificial respiratory volume (at a fixed rate of 54 min-) on cardiac output, its distribution and tissue blood flows were determined with tracer microspheres in control pithed rats or during pressor responses to either the a1-adrenoceptor agonist phenylephrine or the a2-agonist xylazine. Phenylephrine was investigated in the presence of propranolol (3 mg kg 1). The rats were pithed under halothane anaesthesia. 2 A respiratory volume of 15 ml kg-produced modest hypercapnia (Paco2 = 47 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Hyperventilation or hypoventilation was found to cause significant increases or decreases, respectively, in the blood pressure and pulse rate. This phenomenon is not at variance with the effects of blood gases, pH or ventilator stroke volumes on cardiovascular parameters found by others (Nahas & Cavert, 1957, Grant et al, 1985Phillips et al, 1985;MacLean & Hiley, 1988). The changes in pulse rate may result from a reflex increase or decrease in activities of the vagus nerve, the pulmonary stretch mechanoreceptors or cardio-inhibitory centre, or a combination of several of these factors (Daly & Scott, 1958;Evans & Evans, 1968).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Hyperventilation or hypoventilation was found to cause significant increases or decreases, respectively, in the blood pressure and pulse rate. This phenomenon is not at variance with the effects of blood gases, pH or ventilator stroke volumes on cardiovascular parameters found by others (Nahas & Cavert, 1957, Grant et al, 1985Phillips et al, 1985;MacLean & Hiley, 1988). The changes in pulse rate may result from a reflex increase or decrease in activities of the vagus nerve, the pulmonary stretch mechanoreceptors or cardio-inhibitory centre, or a combination of several of these factors (Daly & Scott, 1958;Evans & Evans, 1968).…”
Section: Discussionmentioning
confidence: 63%
“…Dai & Wong (1985) found that in urethane-anaesthetized rats, the effects of adrenaline on blood pressure, and of adrenaline or acetylcholine on pulse rate, were significantly reduced during hypoventilation which induced hypoxaemia, hypercapnia and acidosis. MacLean & Hiley (1988) also revealed that changes in artificial respiratory volume and the attendant blood gas and pH changes caused variations in cardiovascular responses to phenylephrine in the pithed rat.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…When required, pentobarbitone (45mg kg-') was used for anaesthesia and animals artificially ventilated with°2 at a stroke volume of 10mlkg-1, 60min-'; a regimen which has been found to keep blood gases at normal levels (Maclean & Hiley, 1988). Body temperature was maintained at 37.0 + 0.50C by means of a thermocouple linked to a heating lamp.…”
Section: Methodsmentioning
confidence: 99%
“…This may be explained by very slow capillary blood flow, caused by hypotension, arteriolar vasoconstriction and open capillaries (Hardaway, 1985), leading to reduced oxygen delivery and an increase in anaerobic metabolism; the resulting lactic acidaemia causing hypocapnia as CO2 is blown off. Pressor responses to phenylephrine and xylazine, respectively selective agonists at a1-and x2-adrenoceptors, are not affected by changes in blood gases and pH within the range observed after haemorrhage here (MacLean & Hiley, 1988a). Therefore it is unlikely that such changes caused the altered pressor responses to amidephrine and B-HT 933.…”
Section: Discussionmentioning
confidence: 66%